2019
DOI: 10.1097/mrr.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Manual function of the unaffected upper extremity can affect functional outcome after stroke

Abstract: Traditionally, motor deficits of ipsilesional side, generally considered as the unaffected side, have been investigated less and the influence of the impairment is unknown. To evaluate the association between the manual function test (MFT) of nonparetic limb and poststroke functional outcome. We conducted a retrospective analysis of 71 hemiplegic patients with stroke. MFT on both sides was routinely measured at admission and 1 month later after admission by an experienced occupational therapist. The parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Despite the fact that rTMS has been poorly investigated on ipsilesional arm motor recovery after stroke, our findings suggest that it might be an effective treatment of both affected and unaffected upper extremities. This nicely aligns with the increasing number of studies indicating ipsilesional upper extremity impairments after stroke [19], and the recent suggestion that the grip strength of the unaffected arm might be a predictor for short-term motor recovery after stroke with motor training of the unaffected arm having a significant correlation with the functional outcome [30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Despite the fact that rTMS has been poorly investigated on ipsilesional arm motor recovery after stroke, our findings suggest that it might be an effective treatment of both affected and unaffected upper extremities. This nicely aligns with the increasing number of studies indicating ipsilesional upper extremity impairments after stroke [19], and the recent suggestion that the grip strength of the unaffected arm might be a predictor for short-term motor recovery after stroke with motor training of the unaffected arm having a significant correlation with the functional outcome [30].…”
Section: Discussionsupporting
confidence: 81%
“…Despite the small sample, we also performed a small number of tests for upper extremity motor function evaluation. Even though grip strength is considered to be a good indicator of hand function after stroke [30], more tests should be performed since upper extremity function depends not only on muscle strength but also on dexterity, spasticity, range of motion, and proprioception. Many scientists perform a Fugl Meyer Assessment for Upper Extremity (FMA-UE) and Wolf Motor Function Test (WMFT) in stroke rehabilitation since both of these tests are stroke-specific.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unlike other FIM items, no significant body movement is required. Common to the domains of Eating and Grooming is that each involves simple repetitive actions that can be completed with the use of just one hand [36]. However, it could be said that the use of a tool complicates an activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies evaluating the relationship between the functional state of the ipsilesional upper extremity and basic activities of daily living. 9,29,30 As far as we know, our study is the first study in the literature to evaluate the relationship between the functional status of the ipsilesional upper extremity and instrumental activities of daily living. As another important contribution, while most of the previous studies on this subject in the literature evaluated right and left hemiplegia patients under one group and compared their upper extremity functional status with healthy volunteers, right and left hemiplegias were evaluated in separate groups in our study.…”
Section: Contribution Of the Study To The Literaturementioning
confidence: 99%
“…29 Cho et al reported that the basal manual functional state of the ipsilesional upper extremity was correlated with the functional results of the patients and was an important predictor of functional recovery after a 1-month follow-up. 30 Jayasinghe et al reported that functional independence was more related to the grip strength of the ipsilesional upper extremity in patients with left hemisphere damage and to the grip strength of the contralesional extremity in patients with right hemisphere damage, while ipsilesional upper extremity kinematics was associated with functional independence only in the left hemisphere injury group. 31 As a striking result, they reported that the significant effects of the functional state of the ipsilesional upper extremity on functional independence suggest that activities of daily living may be based mainly on the manipulative abilities of the ipsilesional, that is, less affected upper extremity, rather than the contralesional upper extremity.…”
Section: The Relationship Between the Functional Status Of The Unaffe...mentioning
confidence: 99%